Neoliberalism, trade imbalances, and economic policy in the Eurozone crisis - Stockhammer, Engelbert; Constantine, Collin; Reissl, Severin (Nova Economia, 2016)
This paper analyzes the causes of the Eurozone crisis. In doing so, it carefully surveys authors from different economic schools of thought. The paper discusses competing explanations for European current account imbalances. Remarkably, opposing views on the relative importance of cost developments and demand developments in explaining current account imbalances can be found in both heterodox and orthodox economics. Regarding the assessment of fiscal and monetary policy there is a clearer polarisation, with heterodox analysis regarding austerity as unhelpful and most of orthodox economics endorsing it. We advocate a post-Keynesian view, which holds that current account imbalances are not a fundamental cause of the sovereign debt crisis. Rather, the economic policy architecture of the Eurozone, which aims at restricting the role of fiscal and monetary policy, is the key to understanding the crisis in Europe.